2017
DOI: 10.14198/raei.2017.30.05
|View full text |Cite
|
Sign up to set email alerts
|

Contact-induced variation in clausal verb complementation: the case of REGRET in World Englishes

Abstract: It has been argued that in language contact situations both transfer processes from the substrate languages (Thomason, 2008) and cognitive effects derived from the language contact situation itself (Schneider, 2012(Schneider, , 2013 can constitute important catalysts for language variation and change. Regarding the verbal complementation system, Steger and Schneider (2012: 172), for example, notice a preference for finite patterns over non-finite structures in World Englishes (WEs), that is, a preference for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The difference in distribution between L1 and L2 varieties of English has a number of possible explanations, including the cognitive processes involved in the language contact and second language acquisition situations in which these varieties develop (Steger & Schneider 2012), and the influence of substrate languages (Romasanta 2017). Other (Romasanta 2019a), or even 'colonial lag' (Marckwardt 1958), also known by the more neutral term 'extraterritorial conservatism' (suggested by Hundt 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in distribution between L1 and L2 varieties of English has a number of possible explanations, including the cognitive processes involved in the language contact and second language acquisition situations in which these varieties develop (Steger & Schneider 2012), and the influence of substrate languages (Romasanta 2017). Other (Romasanta 2019a), or even 'colonial lag' (Marckwardt 1958), also known by the more neutral term 'extraterritorial conservatism' (suggested by Hundt 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The search query used to find all examples of the verb regret was regret*_v*. This search retrieved a number of false positives and invalid examples, which were discarded (for more details, see Romasanta 2017). A precision and recall analysis was performed to test the accuracy of the data obtained, the results of which were very positive, with values of over 90 percent in almost all varieties, with the exception of BrE (89.2% recall; Romasanta 2019b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article is an attempt to contribute to existing research by looking at the complementation profile of regret, a verb that has been shown to exhibit variation between finite that-clauses and non-finite -ing clauses in earlier periods of English (Heyvaert and Cuyckens 2010;Cuyckens et al 2014;Romasanta 2017Romasanta , 2019Romasanta , 2021aRomasanta , 2021b. In particular, I aim to explore differences in the alternation between that-and -ing complement clauses with the verb regret in American English (AmE) and British English (BrE), as in the examples shown in (1) below, as well as the factors that may influence a speaker's choice of one pattern over the other, as attested in data from the Corpus of Global Web-Based English (GloWbE;Davies 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bernaisch, Gries & Mukherjee 2014;Gries & Bernaisch 2016;Röthlisberger, Grafmiller & Szmrecsanyi 2017;Szmrecsanyi et al 2016), clausal verbal complementation has barely been investigated at all (although cf. Bernaisch 2015;Deshors 2015;Deshors & Gries 2016;García-Castro 2019, 2020Romasanta 2017;Steger & Schneider 2012). Furthermore, these studies have usually concentrated on existing patterns (an exception being new ditransitive verbs; 1 cf.…”
Section: Introductionmentioning
confidence: 99%